PERJANJIAN HUTANG ANTARA PETANI DAN PENGEPUL HASIL PANEN KOPI DI DESA KEMBAHANG LAMA KABUPATEN EMPAT LAWANG DITINJAU DARI FIQH MUAMALAH - Siska, Yeyen; Burhan, Muhammad; Marzuki, Marzuki (Al-muamalah, 2024)
This thesis is entitled Debt Agreements Between Farmers and Collectors of Coffee Harvests in Kembahang Lama Village, Empat Lawang Regency. This thesis answers two questions; First, the form of a debt agreement between farmers and coffee harvesters in Kembahang Lama Village, Talang Padang District, Empat Lawang Regency. Second, namely the Fiqh Muamalah review of the debt agreement between farmers and collectors of coffee harvests in Kembahang Lama Village, Talang Padang District, Empat Lawang Regency. The research used in this research is field research. Sources of data used are primary data sources (obtained through direct observation and interviews with informants) and secondary data sources (obtained through literature on motor vehicle tax, either in the form of books, journals or websites). The result of the discussion is that the Debt Agreement between Farmers and Collectors of Coffee Harvests in Kembahang Lama Village, Empat Lawang Regency is not allowed because there is one condition that is violated, namely the sighat condition.